CLCC1 c. 75C>A Mutation in Pakistani Derived Retinitis Pigmentosa Families Likely Originated With a Single Founder Mutation 2,000–5,000 Years Ago - Ma, Yan; Wang, Xun; Shoshany, Nadav; Jiao, Xiaodong; Lee, Adrian; Ku, Gregory; Baple, Emma L.; Fasham, James; Nadeem, Raheela; Naeem, Muhammad Asif; Riazuddin, Sheikh; Riazuddin, S. Amer; et al. (Frontiers in Genetics, 2022)
Background A CLCC1 c.75C>A (p.D25E) mutation has been associated with autosomal recessive pigmentosa in patients in and from Pakistan. CLCC1 is ubiquitously expressed, and knockout models of this gene in zebrafish and mice are lethal in the embryonic period, suggesting that possible retinitis pigmentosa mutations in this gene might be limited to those leaving partial activity. In agreement with this hypothesis, the mutation is the only CLCC1 mutation associated with retinitis pigmentosa to date, and all identified patients with this mutation share a common SNP haplotype surrounding the mutation, suggesting a common founder. Methods SNPs were genotyped by a combination of WGS and Sanger sequencing. The original founder haplotype, and recombination pathways were delineated by examination to minimize recombination events. Mutation age was estimated by four methods including an explicit solution, an iterative approach, a Bayesian approach and an approach based solely on ancestral segment lengths using high density SNP data. Results All members of each of the 9 families studied shared a single autozygous SNP haplotype for the CLCC1 region ranging from approximately 1 Mb to 3.5 Mb in size. The haplotypes shared by the families could be derived from a single putative ancestral haplotype with at most 2 recombination events. Based on the haplotype and Gamma analysis, the estimated age of the founding mutation varied from 79 to 196 generations, or approximately 2,000-5,000 years, depending on the markers used in the estimate. The DMLE (Bayesian) estimates ranged from 2160 generations assuming a population growth rate of 0 to 309 generations assuming a population growth rate of 2% with broad 95% confidence intervals. Conclusions These results provide insight into the origin of the CLCC1 mutation in the Pakistan population. This mutation is estimated to have occurred 2000-5000 years ago and has been transmitted to affected families of Pakistani origin in geographically dispersed locations around the world. This is the only mutation in CLCC1 identified to date, suggesting that the CLCC1 gene is under a high degree of constraint, probably imposed by functional requirements for this gene during embryonic development.